Nexus Between Pocket Money, Peers, and Financial Management: The Role of Financial Literacy - Praticia Rahman; Putra Hilmi Prayitno; Wahjoedi Wahjoedi; Lisa Rokhmani (Jurnal Pendidikan Ekonomi, 2024)
Financial management has been an issue among Indonesian and educational institution have attempted to enhance financial literacy, especially for high school students. This study aims to examine the effect of pocket money and peers on financial management, with financial literacy as an intervening variable. This study involved primary data from a sample of 102 high school students using a purposive sampling technique. To collect data, the researchers distributed questionnaires via Google Forms. By using the SEM-PLS, the results indicated that pocket money, peers, and financial literacy have an effect on student financial management. Indeed, pocket money and peers have a positive and significant effect on student financial literacy. Furthermore, financial literacy successfully intervenes in the effect of pocket money and peers on student financial management. The implications of this research can be used for educational institutions so that students are better prepared to face financial challenges in the future and are able to manage finances wisely.   Keywords: pocket money, peers, financial management, financial literacy